Criminal Liability for Unintentional Homicide: A Comparative Study of Islamic and Indonesian Law - Alhadi Fadhli; Ruslan Abdul Gan; Rahmi Hidayati (CV. AFDIFAL MAJU BERKAH, 2026)
This research examines criminal liability in cases of unintentional homicide through a comparative study between Islamic criminal law and Indonesian positive criminal law at the Jambi District Court. Unintentional homicide is an act that results in the loss of human life without malicious intent, yet it raises serious legal issues regarding criminal responsibility. In Indonesian positive criminal law, such acts are classified as negligence offenses under Article 359 of the Criminal Code, with sanctions in the form of imprisonment or confinement. In contrast, Islamic criminal law recognizes the concept of qatl al-khaṭā’, which emphasizes moral and social responsibility through the payment of diyat and the fulfillment of kafarat without the application of retaliatory punishment. This study aims to analyze the implementation of criminal liability for unintentional homicide under positive criminal law, examine the concept of criminal liability from the perspective of Islamic criminal law, and compare their similarities, differences, and implications for criminal justice reform. The research employs an empirical juridical method with a qualitative approach, using literature review, analysis of legislation and court decisions, and interviews with judges at the Jambi District Court. The findings show that positive criminal law remains predominantly punitive and offender-oriented, while Islamic criminal law offers a more restorative approach focused on victim recovery and social harmony. This study concludes that restorative justice values in Islamic criminal law are relevant for reformulating criminal liability in unintentional homicide cases to promote a more humane, proportional, and just national criminal justice system